2011
DOI: 10.1111/j.1747-0285.2011.01170.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Agents that Induce Apoptosis of Multicellular Tumour Spheroids: Enrichment for Mitotic Inhibitors with Hydrophobic Properties

Abstract: Cell-based anticancer drug screening generally utilizes rapidly proliferating tumour cells grown as monolayer cultures. Hit compounds from such screens are not necessarily effective on hypoxic and slowly proliferating cells in 3-D tumour tissue. The aim of this study was to examine the potential usefulness of 3-D cultured tumour cells for anticancer drug screening. We used colon carcinoma multicellular spheroids containing hypoxic and quiescent cells in core areas for this purpose. Three libraries (∼11 000 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…NSC647889 shows antiproliferative activity in the NCI60 cell panel (average GI50: 1.1 µM; strongest activity on acute lymphoblastic leukaemia, promyelocytic leukemia and chronic myelogenous leukemia cell lines (http://dtp.nci.nih.gov/)). We previously reported that compounds active on multicellular spheroids generally are hydrophobic [19] and the hydrophobicity (XLogP 7.3) of NSC647889 is consistent with this observation. The high degree of hydrophobicity complicated systematic in vivo assessments of antineoplastic effects.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…NSC647889 shows antiproliferative activity in the NCI60 cell panel (average GI50: 1.1 µM; strongest activity on acute lymphoblastic leukaemia, promyelocytic leukemia and chronic myelogenous leukemia cell lines (http://dtp.nci.nih.gov/)). We previously reported that compounds active on multicellular spheroids generally are hydrophobic [19] and the hydrophobicity (XLogP 7.3) of NSC647889 is consistent with this observation. The high degree of hydrophobicity complicated systematic in vivo assessments of antineoplastic effects.…”
Section: Discussionsupporting
confidence: 75%
“…Sectioned spheroids were incubated with Hypoxyprobe-1 (HPI Inc., Burlington, MA, USA) to detect pimonidazole adducts. Serial sectioning was not required since the hanging drop procedure generates spheroids of homogenous size [19].…”
Section: Immunological Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, if uniform and equal in size, MTCS can be used for drug activity comparisons (8,13). We have previously shown that compounds identified in 3D-model screens are distinct from those found using 2D models (14,15). Thus, tumor cells in 3D models are not necessarily always drug resistant, opening a possibility for identification of more active cancer drugs if large-scale 3D-based drug screening could be pursued.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous MCTS formation methods (14,(16)(17)(18)(19)(20) but most are not suited for high-throughput screening (HTS); they are either costly, difficult to handle in a large scale or the spheroids often vary in size and number. Thus, MCTS-based screening efforts performed so far have used small drug libraries, not exceeding a few hundred compounds (14,15,17,21).…”
Section: Introductionmentioning
confidence: 99%